Designing and Conducting Qualitative Studies in ELT: Methods and Practices - Pandey, Gopal Prasad (International Journal of Social Sciences and Management, 2025)
Qualitative research (QR) in ELT provides an essential lens for examining the complexities of language learning, teaching practices and classroom interactions in natural contexts. This study explores the significance, theoretical foundations and methodological approaches of qualitative inquiry, emphasizing its focus in interpretivist and constructivist paradigms. It examines key research methods, including case studies, ethnography, and narrative inquiry, while situating qualitative research within its historical and epistemological context. Using a document analysis approach, the study systematically reviews existing literature and applies inductive thematic analysis to identify emerging trends and methodological advancements. The paper discusses the key characteristics of QR along with the guiding principles of qualitative data analysis in ELT and applied linguistics research. The findings highlight the increasing relevance of qualitative research in understanding teacher-student interactions, second language acquisition, and pedagogical decision-making, as well as the growing integration of digital tools like Computer-Aided Qualitative Data Analysis Software (CAQDAS) to enhance analytical rigor. This study contributes to the broader discourse on qualitative methodologies in ELT and Applied Linguistics by reinforcing their theoretical depth and practical applicability. It advocates for continued methodological innovation and interdisciplinary research to expand the impact of qualitative inquiry on language education. Int. J. Soc. Sc. Manage. Vol. 12, Issue-2: 114-122.